Pengaruh Knalpot Racing Pada Kendaraan Roda Dua Yang Bising Di Kota Bima - Surip, Surip; Hendra, Hendra; Junaidin, Junaidin; Asmiatiningsih, Sri; Muhamadong, Muhamadong (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
In the midst of a pluralistic community life as problems occur that require legal resolution, so that the settlement has certainty. The complexity of legal issues becomes very dilemmatic. Even the law lags far behind when compared to the current incidence of crimes and offenses. However, amid the complexity of violations and crimes today, the law must provide legal certainty and a sense of security in society. One of the violations that concerns violations of technical requirements and roadworthiness is the use of exhaust racing / not stanfdar which directly shows an attitude of not having traffic ethics, where the use of "exhaust racing" violates Law Number 22 of 2009 concerning Road Transport Traffic.  By conducting raids on the control of two-wheeled motorized vehicles with noise, it is hoped that there will be legal awareness of the public to return to using standard knalopt so that it can reduce pollution that arises and can realize the comfort of fellow road users.